The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/his.14023
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinicopathologic and molecular spectrum of BCOR‐associated sarcomas in adults

Abstract: Aims BCOR gene alteration is a genetic signature of rare subsets of sarcomas. Most BCOR‐associated sarcomas thus far reported are in the pediatric population, except for uterine sarcomas. We studied seven cases of BCOR‐associated non‐uterine sarcomas in adult patients. Methods and results The patients were four men and three women ranging from 26 to 71 years in age. Three tumors, two of which primarily affected the kidney, showed BCOR‐CCNB3. One tumor with a ZC3H7B‐BCOR occurred in the chest wall, and a tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…[ 2 ] Significant up-regulation of NTRK3 was also recently documented in a small subset of BCOR -associated sarcomas in adults harboring BCOR - CCNB3 , ZC3H7B - BCOR , CIITA - BCOR , and BCOR ITD. [ 8 ] In keeping with this finding, an earlier molecular study using Affymetrix U133A data showed high NTRK3 expression in CCSK, the renal counterpart of BCOR family tumors. [ 15 ] More recent investigations exploring the specificity and sensitivity of pan-Trk immunostaining across various tumor types have also included a few BCOR -associated sarcomas.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…[ 2 ] Significant up-regulation of NTRK3 was also recently documented in a small subset of BCOR -associated sarcomas in adults harboring BCOR - CCNB3 , ZC3H7B - BCOR , CIITA - BCOR , and BCOR ITD. [ 8 ] In keeping with this finding, an earlier molecular study using Affymetrix U133A data showed high NTRK3 expression in CCSK, the renal counterpart of BCOR family tumors. [ 15 ] More recent investigations exploring the specificity and sensitivity of pan-Trk immunostaining across various tumor types have also included a few BCOR -associated sarcomas.…”
Section: Discussionmentioning
confidence: 60%
“…Intriguingly, up-regulated NTRK3 mRNA expression was demonstrated in all of the 4 tumors with KMT2D - BCOR (n=2), BCOR - CHD9 (n=1), or CIITA - BCOR (n=1) fusions. [ 2 , 8 ] Three of the cases tested in this study were all positive for pan-Trk, including the BCOR - CHD9 case with negative BCOR staining, suggesting that NTRK3 expression is not affected by different exon composition of BCOR fusions. Of note, in all tumors reported to date with KMT2D - BCOR , BCOR - CHD9 , or CIITA - BCOR fusions, reciprocal fusion transcripts have been identified.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…18 Additional gene fusions involving BCOR have also been subsequently found, including BCOR-ITD (internal tandem duplication), BCOR-MAML3, ZC3H7B-BCOR, BCOR-KMT2D, and CIITA-BCOR. [19][20][21][22] BCOR-CCNB3 sarcomas more frequently arise in bone than soft tissue, have a striking predilection for children and young adults (.90% younger than 20 years), and are male predominant. BCOR-ITD tumors occur preferentially in the somatic soft tissue of the trunk, abdomen, and head and neck, sparing the extremities.…”
Section: Sarcoma With Bcor Genetic Alterationsmentioning
confidence: 99%